Tradisi “Toron” sebagai Media Penanaman Semangat Silaturrahmi dan Toleransi Masyarakat Madura - Mahbubah, Latifatul (Proceedings of Annual Conference for Muslim Scholars, 2025)
Toron is an annual socio-cultural phenomenon in which Madurese migrants from various regions return to their hometowns, especially before Islamic holidays. This study aims to analyze and describe the role and meaning of the Madurese tradition of homecoming in the context of strengthening ties and fostering tolerance amidst the social diversity of the Madurese community. This study is a qualitative study in which data collection uses interviews, documentation, and observation. The results show that the tradition and culture of "toron" for the Madurese community has important values ​​in life, one of which is that "toron" is an important medium for establishing ties between families and neighbors, becoming a medium for fostering an attitude of tolerance towards any differences that exist, both in terms of beliefs and traditions that apply in two different regions such as the traditions that apply in Madura and Jakarta as places of migration.